High level transferable resistance among Escherichia coli - AHMAD, IQBAL; YADAVA, J N S; AHMAD, SHAMIM (The Indian Journal of Animal Sciences, 2013)
Escherichia coli strains (48) isolated from clinical cases of man and animals were screened for their antibiotic resistance profile and their potential to exchange their chromosomal chromosomal genetic materials (R-plasmids). Of these 32 (66.66%) strains were resistant to one or more drugs. Multiple resistance was observed in 26 (81.56%) strains. Maximum number of strains were resistant to streptomycin (64.41%) followed by ampicillin (56.25%). tetracycline (52.83%). amoxycillin (50%). chloramphenicol (41.66%) and co-trimoxazole (37.31%), and least to kanamycin (10.41 %), nitrofurantoin and nitrofurazone (8.33% each). None of the strans were resistant to nalidixic acid: 13 multi-resistant strams could transfer their drug resistance markers to the recipient E. coli K 12 J 62-1. These transferred R-factors were stable for several generations. Strains possessing single. double or triple drug-resistant markers were mostly non-transferable by conjugation experiments in vitro.